Polycystic ovarian syndrome: need for life course approach - Dahiya, Neha; Bharti, Aakanksha; Vats, Kritika; Bachani, Damodar (International Journal Of Community Medicine And Public Health, 2020)
Polycystic ovarian syndrome (PCOS) is one of the leading but treatable causes of infertility among women. PCOS is a heterogeneous condition therefore it involves multiple disciplines and there is a wide research and clinical agenda. The prevalence of PCOS in India among 15-24 year old adolescents and young girls was found by Rotterdam criteria to be 22.5% and by Androgen Excess Society criteria to be 10.7%. Earlier it was considered only as a reproductive disorder but now it includes metabolic and psychological features as well. Under diagnosis of PCOS remains to be problematic. This is a complex syndrome and has an influence throughout the lifespan and requires multidisciplinary treatment approach as well as self-management. The life course approach or life course theory or the life course perspective was explored in 1960’s. In this approach individual's lives are analyzed within structural, social, and cultural contexts.